Improvements in single‐use bioreactor film material composition leads to robust and reliable Chinese hamster ovary cell performance. (6th May 2019) - Kelly, Paul S.; Dorival‐García, Noemi; Paré, Samantha; Carillo, Sara; Ta, Christine; Alarcon Miguez, Antonio; Coleman, Orla; Harper, Emma; Shannon, Maeve; Henry, Michael; Connolly, Lisa; Clynes, Martin; et al.
Abstract: Single‐use technologies, in particular disposable bioreactor bags, have become integral within the biopharmaceutical community. However, safety concerns arose upon the identification of toxic leachable compounds derived from the plastic materials. Although the leachable bis(2, 4‐di‐tert‐butylphenyl)‐phosphate (bDtBPP) has been previously shown to inhibit CHO cell growth, it is critical to determine if other compounds like this are still present in subsequent generations of films for industrial application. This study compares the performance of CHO cells, CHO‐K1, and CHO‐DP12, cultured in media conditioned in an older single‐use bioreactor (SUB) film (F‐1) and a newer generation film (F‐2) from the same vendor. CHO cells cultured in media conditioned for 7 days in the F‐1 film demonstrated significantly reduced growth and antibody productivity profiles when compared to controls and media conditioned for the same time period in the newer F‐2 film. Proteomic profiling of CHO cells cultured in the F‐1 conditioned media identified differentially expressed proteins involved in oxidative stress response as well as compromised ATP synthesis. These potentially metabolically compromised cells exhibited reduced oxidative phosphorylation activity as well as lower glycolytic metabolism, characteristic of slower growing cells. Nonvolatile and metal leachables analysis of film extracts by LC–MS revealed a reduction in the abundance of the analyzed leachates from F‐2 films when compared to F‐1 films including bDtBPP, potentially explaining improved CHO cell growth in F‐2 conditioned media. Furthermore, in vitro endocrine disruptor testing of the known leachable revealed this molecule to possess the potential to act as an androgen antagonist. This study demonstrates an improvement in the materials composition used in modern generations of SUBs for safe application in the bioprocess.